Connection Inspection Blood Routine With Status History of Malaria at Ibnu Sina Hospital Makassar 2019-2024 - M Farhan Anwar; Irna Diyana Kartika Kamaluddin; Berry Erida Hasbi; Indah Lestari daeng Kanang; Irmayanti Irmayanti (Jurnal EduHealth, 2025)
Malaria remains serious health problems in Indonesia, especially in the eastern region which has a high incidence . Routine blood tests are used to identify hematological abnormalities in malaria patients and the status of malaria history which is suspected to have a role in hematological changes , this is not fully understood . Therefore , it is necessary to explore the effect malaria history status on routine blood test results . To analyze the relationship between routine blood test results (hemoglobin, platelets , leukocytes ) and malaria history status in patients at Ibnu Sina Hospital Makassar during the period 2019-2024. Observational analytical design with a cross-sectional approaches . There were 43 patients diagnosed with malaria. Data were analyzed using the chi-square statistical test . The majority of malaria patients were aged 21-30 years and were dominated by man while the most common type of plasmodium was P. vivax and occurred in patients without a previous history of malaria. Routine blood results found that most Patients had normal hemoglobin (76.70%), thrombocytopenia (83.70%), and normal leukocytes levels (72.10%). These results indicate a significant relationship between malaria history and hemoglobin levels (p = 0.020) and platelet count (p = 0.010) because malaria patients who have a history of malaria already have partial immunity that can minimize the occurrence of hematological disorders . However , in leukocytes , there was no significant relationship between malaria history and leukocyte count (p = 0.503). A significant relationship was found between hemoglobin and platelets with malaria history status .